Characterisation of plasticised PVDF-HFP polymer electrolytes - Majid, Siti Rohana; Arof, Abdul Kariem; Noor, M.M.; Careem, M.A. (Springer Verlag (Germany), 2011)
This study focuses on the preparation and characterisation of sodium ion conducting polymer electrolytes. Poly(vinylidenefluoride-co-hexafluoropropylene) has been used as the host matrix and hydrated sodium sulphide (Na(2)S center dot 9H(2)O) salt as the source of charge carriers in the polymer electrolyte system. To the highest conducting polymer-salt electrolyte, different concentrations of equal weight of propylene carbonate and diethyl carbonate mixture have been added, and the electrolytes have been characterised by X-ray diffraction, Fourier transform infrared spectrometry, scanning electron microscopy and electrochemical impedance spectroscopy. The room temperature ionic conductivity of 1.3 x 10(-4) S cm(-1) for the unplasticised electrolyte with a composition of 65 wt-% poly(vinylidenefluoride-co-hexafluoropropylene)-35 wt-% Na(2)S increased to 3.49x10(-4) S cm(-1) when 30 wt-% propylene carbonate/diethyl carbonate (w/w=1) plasticisers were added.